Dynamic relationship between China’s inward and outward foreign direct investments - Yao, Shujie; Wang, Pan; Zhang, Jing; Ou, Jinghua (Elsevier, 2016)
This paper studies the dynamic relationship of China’s inward and outward foreign direct investments (FDI). It first identifies the key determinants of China’s outward FDI (OFDI) in 172 host countries during 2003-09 using a partial stock adjustment model. It finds strong evidence of dynamic adjustment in China’s OFDI stock with an agglomeration effect. The dynamic adjustment and agglomeration effects are stronger in “high-tech” countries than in “low-tech” ones but indifferent in host country’s resource endowments and income levels. The empirical results suggest that there exists a substantial adjustment cost in China’s OFDI and that China’s existing OFDI stock can gradually adjust towards its long term equilibrium level, which is not only greater but also more volatile than the actual stock. Of particular interest is that we find a strong and positive relationship between lagged inward FDI (IFDI) and contemporaneous OFDI, implying that capital outflow from China has been partially induced by the countries which have invested in China.